Proteomic phenotyping of metastatic melanoma reveals putative signatures of MEK inhibitor response and prognosis. Issue 6 (11th September 2018) - Krisp, Christoph; Parker, Robert; Pascovici, Dana; Hayward, Nicholas; Wilmott, James; Thompson, John; Mann, Graham; Long, Georgina; Scolyer, Richard; Molloy, Mark
Abstract Background Genotyping of melanomas is used to identify patients for treatment with BRAF and MEK inhibitors, but clinical responses are highly variable. This study investigated the utility of protein expression phenotyping to provide an integrated assessment of gene expression programs inBRAF/NRAS melanoma which would be useful for prognosis and may predict response to MEK inhibition. Methods Mass spectrometry profiling of early passage cell lines established from Stage III cutaneous melanomas was conducted. Basal protein expression was correlated with in vitro response to the MEK inhibitor, selumetinib. Protein expression in a cohort of 32 drug naïveBRAF/NRAS metastatic melanoma specimens was examined. The prognostic utility of a subset of these proteins and mRNA transcripts from a separate cohort was determined. Results Unsupervised analysis of basal cell line protein abundances delineated response to selumetinib, butBRAF/NRAS genotype did not. Resistance was associated with functions including cell motility, cell adhesion and cytoskeletal organization. Several of these response biomarkers were observed in lymph node biospecimens and correlated with melanoma-specific survival. Loss of ICAM-1 protein and mRNA expression was a strong prognosticator of diminished survival inBRAF/NRAS mutant melanoma. Conclusions These results demonstrate the utility of proteomic phenotyping to identify both putative biomarkers of response to MEK inhibition and prognostication associated with metastatic melanoma.